THE INFLUENCE OF DIRECTING FUNCTION OF NURSE UNIT MANAGER AND TEAM LEADER TO THE NURSE JOB CONTENTMENT AMONG STAFF NURSES IN BLAMBANGAN DISTRICT GENERAL HOSPITAL BANYUWANGI - Achmad Sigit S (University of Muhammadiyah Malang, 2011)
The service of treatment at the general hospital of Blambangan not yet run optimal prima service. Activity of MPKP and guidance function in room of VIP as sample room and room take care of to lodge other not yet been run consistently. Take care unit of to lodge class three still use functional method. The aim of this study was to investigate the influence of directing function of nurse unit manager and team leader to the nurse job contentment among staff nurses in general hospital ofBlambangan and general hospital of Dr Haryoto Lumajang. The method was a quasi experiment, prepost test with control group design. The data gathered before and after the directing function (hand over, pre conference, post conference, motivational climate, supervision and delegation) had trainedand guided to the nurse unit manager and team leader in general hospital of Blambangan. The samples determined by purposive sampling. They were 35 nurse staff of general hospital of Blambangan (experimental group) and 40 nurse staff of general hospital of Dr Haryoto (control group). The instrument was a questionnaire consisted 36 of likert scale statements adopted from Minnesota satisfaction questionnaire. The result showed that the level of nurse job satisfaction in theexperimental group increased higher significantly than the control group (p = 0,000;  = 0,005). Putting the directing function into action consistently in the daily nursing practice improved the probability of the nurse job satisfaction level about 67,40% and enhanced it around 16,746 point. Theday-to-day maintaining their job satisfaction level should be done through MPKP jiwa modification sub directing function so that they will deliver high-quality nursing care in general hospital of Blambangan.